Avaliação dosimétrica de protocolos de exame de tomografia computadorizada de feixe cônico - Soares, Maria Rosangela (2016)
This PhD thesis, addresses the issue of evaluation of cone beam computed tomography, CBCT, scanning protocols, was introduced in dental radiology at the end of the 1990s, and it quickly became a fundamental examination for various procedures. Its main characteristic, the difference of medical CT is the beam shape. This study aimed to calculate the absorbed dose in eight tissues / organs of the head and neck, and to estimate the effective dose in 13 protocols and two techniques (stitched FOV e single FOV) of 5 equipment of different manufacturers of cone beam CT. For that purpose, a female anthropomorphic phantom was used, representing a default woman, in which were inserted thermoluminescent dosimeters at several points, representing organs / tissues with weighting values presented in the standard ICRP 103. The results were evaluated by comparing the dose according to the purpose of the tomographic image. Among the results, there is a difference up to 325% in the effective dose in relation to protocols with the same image goal. In relation to the image acquisition technique, the stitched FOV technique resulted in an effective dose of 5.3 times greater than the single FOV technique for protocols with the same image goal. In the individual contribution, the salivary glands are responsible for 31% of the effective dose in CT exams. The remaining tissues have also a significant contribution, 36%. The results drew attention to the need of estimating the effective dose in different equipment and protocols of the market, besides the knowledge of the radiation parameters and equipment manufacturing engineering to obtain the image.